Phytoplankton and zooplankton composition in mangroves of the Mendana Strait, Johor River, Johor, Malaysia - Kassim, Zaleha; Ahmad, Zuhairi; Shammodin, Muhammad Shaheed; Wan Johari, Wan Siti Mardhiah; Ismail, Ahmad (Malayan Nature Society, 2020)
Mangrove forest of Kong Kong lies along Mendana Strait occupying Kampung Kong Kong, Kampung Sungai Latoh and the adjacent Pulau Juling where most of the mangrove trees are still at the growing stage. There are increasing number of recreational and ecotourism activities in the straits since the area has been included in the ecotourism development plan for Johor. Those activities could affect the water body which could possibly be indicated by the plankton community. The plankton composition study of the mangroves was carried out in April-May 2018. The triplicate samples were obtained each month by vertically hauled the phytoplanktons (40 microns) and zooplanktons (100 microns) net from 1 m depth of the river. Phytoplankton community comprised of at least 14 species and was dominated by Ceratium (40%) in April but replaced by Skeletonema (31%) in May. The results showed that Copepoda has dominated the water bodies for both months. Three genera of Copepoda and crustacean larval forms were found, including Calanoida, Cyclopoida, Harpacticoida, copepoda nauplii and cirripedia nauplii. There was no significant correlation between phyto- and zooplankton with the environmental parameters (p>0.05). This is possibly due to the significant existence of the thick mangroves in the Strait of Mendana. A long-term data collection could improve the results and understanding on the response of plankton community to environmental condition in mangrove ecosystem.